Impulse response estimation via flexible local projections - Haroon Mumtaz; Michele Piffer (Queen Mary University of London, School of Economics and Finance, 2022)
This paper introduces a exible local projection that generalises the model by Jordà (2005) to a non-parametric setting using Bayesian Additive Regression Trees. Monte Carlo experiments show that our BART-LP model is able to capture non-linearities in the impulse responses. Our first application shows that the fiscal multiplier is stronger in recession than expansion only in response to contractionary fiscal shocks, but not in response to expansionary fiscal shocks. We then show that financial shocks generate effects on the economy that increase more than proportionately in the size of the shock when the shock is negative, but not when the shock is positive.
Keywords: C14; C11; C32; E52; 330; Non-linear models; non-parametric techniques; identification